2004
DOI: 10.1142/s1088424604000246
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of enzymatic activity for myoglobins by modification of heme-propionate side chains

Abstract: The modification of myoglobin is an attractive process not only for understanding its molecular mechanism but also for engineering the protein function. The strategy of myoglobin functionalization can be divided into at least two approaches: site-directed mutagenesis and reconstitution with a non-natural prosthetic group. The former method enables us to mainly modulate the physiological function, while the latter has the advantage of introducing a new function on the protein. Particularly, replacement of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…myoglobins. A propionate-flavin reconstituted hemin, for example, showed for the first time a ferric peroxoanion intermediate in myoglobin [36]. In a similar fashion, early work by Ghosh et al [37] showed a mixing of spin densities between porphyrin and aryl derivatives orbitals.These studies indicate that modification of the heme-propionate side chains with electron rich groups can be a new and effective way to engineer functions for the hemoproteins.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…myoglobins. A propionate-flavin reconstituted hemin, for example, showed for the first time a ferric peroxoanion intermediate in myoglobin [36]. In a similar fashion, early work by Ghosh et al [37] showed a mixing of spin densities between porphyrin and aryl derivatives orbitals.These studies indicate that modification of the heme-propionate side chains with electron rich groups can be a new and effective way to engineer functions for the hemoproteins.…”
Section: Introductionmentioning
confidence: 79%
“…This interaction is analogous to that of Asp297 in CYP101 (further discussed below). Direct chemical modification of the propionate groups by Hayashi et al [34] has shown enhanced ligand dissociation and peroxidase (and peroxygenase) activities [35,36] for the reconstituted Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the increasing focus on heme propionate modification as a means of achieving specific chemical derivatization of myoglobin in the development of new chemical properties [60][61][62][63][64][65][66] and the study of electron transfer reactions with other proteins [67,68], the structural and functional consequences of such modifications to the protein that may be induced at positions remote from the site of chemical modification may merit further consideration. Table 1 pK a values for His residues of native and DME-metheme substituted horse heart Mb determined by 1 (3) The assignments of the peaks labeled in Fig.…”
Section: Discussionmentioning
confidence: 99%